Neuropsychiatric manifestations of monkeypox: A clinically oriented comprehensive review - Yashendra Sethi; Pratik Agarwal; Hamsa Murli; Summaiya Waheed; Sajeda Ghassan Matar; Mohamed Baklola; Hitesh Chopra; Talha Bin Emran; Elfatih A. Hasabo (Brain and Behavior, 2023)
Abstract Monkeypox (MPX) has emerged as a threatening outbreak in recent months. The understanding of disease pathogenesis and its systemic involvement has evolved with time. Both the virus and its vaccine, like other members of the Orthopoxvirus family, were always expected to have neuropsychiatric consequences. Several neurological complications have been reported with MPX and its vaccines that include but not limited to headaches, myalgia, encephalitis, and coma. Psychiatric complications like anxiety and depression have also been reported; however, we lack evidence to present a direct causality. We conducted a literature review to compile recent evidence on neuropsychiatric manifestations and underline the importance of evolving aspects and complications of MPX. We advocate for better reporting of cases and adverse events, to enhance our understanding of the disease, aiding physicians to make more informed decisions, thus facilitating timely diagnosis and treatment.